Transformation of ferromagnetic properties in Fe\(_3\)O\(_4\) to \(α-Fe_2O_3\) by the polyol process and heat treatment - Nguyen, Thi Nhat Hang; Le , Hong Phuc; Ho , Van Cuu; Nguyen, Huu Tri; Long, Nguyen Viet (Communications in Physics, 2024)
This study investigates the transformation of ferromagnetic properties of Fe3O4 to \(α\)-Fe2O3 through the polyol process and subsequent heat treatment. Structural and magnetic changes were analyzed via X-ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM), revealing significant phase transitions and magnetic property variations.